ChemInform Abstract: Research Development on the Preparation of NiFe Magnetic Nanoparticles. Issue 49 (December 2015) - Liu, Yan; Chi, Yanxiu; Li, Xinyan; Wang, Shuai; Lin, Sheng
Abstract: Review: 23 refs.